VIDEO â€œNEU IN BERLIN-DIE ERSTE BEGEGNUNGâ€ SEBAGAI MATERI AJAR TAMBAHAN UNTUK PEMBELAJARAN MENYIMAK BAHASA JERMAN SISWA SMA - BELA RIMBA, BADAI (LATERNE, 2016)
Listening is one of language skill which is learnt in the tenth grade of senior high school. In proccess, it is need to use an effective media to reach the purpose of learning. Audio visual like video is being one alternatif  media. Video entitled ,neu in berlin die erste begegnung form www.lingorilla is being the choice. Problems of the study  for this research is : 1. Can the “Neu in Berlin-Die erste Begegnung” be used as additional material in part listening of german subject for the tenth grade senior high school in the first semester?  The purpose of this research is to describe the analyze of “Neu in Berlin-Die erste Begegnung”  video as additional material in part listening of german subject for the tenth grade senior high school in the first semester. This research use qualitative method with documentation technique.                 The analysis shown that the video is suitable with 6 criterias to choosing audio visual learning material. (1). The relevancy between material and students competence.The dialogue in the video is suitable with thqe participants which is consist of prasen, personal pronomen, frageworter and wortschatz.(2). Suitablility of basic competence.In video there are some dialogues which is suitable withbasic competence for the participants. The dialogues are about the way to understand and to ask a fact, feel and attitude, and order n offer something which has connection with identity.(3). It's packed in interesting story.The story in the video is played by germany and it's same with daily activities in german, so the students can understand how the german having communication everyday. It can be an example to introduce itself using germany.(4). The truth of material. This video comes from lingorilla sitewhich can be accessed from all the world so the truth can be responsible. (5). The màximal duration is 20 minute. The video's duration is 2:35, it's clear, brief and not too long. (6). It is suitable with the theme. This video tells about how to introduce itself, it includes in personal identity. Based on the result, it can be concluded. That “ Neu in Berlin-Die erste Begegnung” video can be used as additional materials in listening part for german subject in the first semester students in tenth grade of Senior High School.   Keywords : Video, Additional Material, Listening session